LEGAL ANALYSIS OF THE PROTECTION OF THE RIGHTS OF VICTIMS OF THE CRIME OF HUMAN TRAFFICKING - Hermanto (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2022)
This study aimed to analyze the law on protecting the rights of victims of the crime of human trafficking. This research uses normative juridical analysis and a statute approach. The sources of law in this study are based on primary and secondary sources of law, which refer to the norms contained in the legislation. Then the research results are described systematically to answer the questions that have been asked. Analysts of legal materials in this study use a grammatical-interpretation method, namely interpretation according to the grammar and words used for legislators to state their objectives. To protect the rights of victims of human trafficking, there are still dualisms in the TIP law and the Criminal Procedure Code in settlement of restitution for victims. This makes solving the problem of human trafficking difficult. In this case, it is necessary to review the substance of the TIP law; this is due to other issues as contained in this law.